Proceedings of IEEE International Computer Performance and Dependability Symposium
DOI: 10.1109/ipds.1996.540223
|View full text |Cite
|
Sign up to set email alerts
|

SPN2MGM: tool support for matrix-geometric stochastic Petri nets

Abstract: In this paper we present the tool SPN2MGM that can be used to construct and solve stochastic Petri nets using matrix-geometric techniques. The tool automatically recognizes the "matrix-geometric structure" of the Markov chain underlying the stochastic Petri net, and solves the Markov chain with these well-known and efficient techniques.W e informally characterize the class of stochastic Petri nets of interest (a formal definition has been given in an earlier paper) after which we briefly touch upon the matrix-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…We resorted to the the tool SPN2MGM [21,22] to perform several case studies, where we observed a number of peculiarities (see next section) that led to the current paper.…”
Section: Continuousmentioning
confidence: 99%
See 1 more Smart Citation
“…We resorted to the the tool SPN2MGM [21,22] to perform several case studies, where we observed a number of peculiarities (see next section) that led to the current paper.…”
Section: Continuousmentioning
confidence: 99%
“…SPN2MGM allows to derive reward-based performance measure from iSPNs by applying efficient solution algorithms to solve the underlying quasi-birth-and-death Markov chains. For further details on iSPNs, we refer to [21,22,31].…”
Section: The Psst Model In Queueing Analysesmentioning
confidence: 99%